Impact of homologous and heterologous boosters in neutralizing antibodies titers against SARS-CoV-2 Omicron in solid-organ transplant recipients - Gaete-Argel, Aracelly; Saavedra-Alarcón, Vicente; Sauré, Denis; Alonso-Palomares, Luis; Acevedo, Mónica L.; Alarcón, Marion; Bueno, Susan M.; Kalergis, Alexis M.; Soto-Rifo, Ricardo; Valiente-Echeverría, Fernando; Cortes, Claudia P. (Frontiers in Immunology, 2023)
Booster doses of SARS-CoV-2 vaccines improve seroconversion rates in solid organ transplant recipients (SOTRs) but the impact of homologous and heterologous booster doses in neutralizing antibody (NAb) titers and their ability to interfere with the variant of concern Omicron are not well studied. We designed a prospective, open-label, observational clinical cohort study. 45 participants received two doses of BNT162b2 or CoronaVac (21-day or 28-day intervals, respectively) followed by a first and second booster with BNT162b2 (5-month apart each) and we analyzed the neutralizing antibody titers against SARS-CoV-2 D614G (B.1 lineage) and Omicron (BA.1 lineage). Our results show that SOTRs receiving an initial two-dose scheme of CoronaVac or BNT162b2 generate lower NAbs titers against the ancestral variant of SARS-CoV-2 when compared with healthy controls. Although these NAb titers were further decreased against the SARS-CoV-2 Omicron, a single BNT162b2 booster in both groups was sufficient to increase NAb titers against the variant of concern. More importantly, this effect was only observed in those participants responding to the first two shots but not in those not responding to the initial vaccination scheme. This information should be considered when planning booster vaccination programs in this risk group.